Minority Contact Varieties of Hungarian, with a Special Review of Varieties in the Area of Ex-Yugoslavia - Žagar Szentesi, Orsolya (Array, 2008)
Following a brief overview of numerical and spatial distribution of Hungarian indigenous minorities in the Carpathian basin, the first part of the article refers to revised scholarly (sociolinguistic primarily) importance of the so-called contact varieties of the Hungarian language outside borders since the beginning of the 90s, including comparative reviews of equivalent varieties of Croatian abroad. Goals and results achieved so far by sociolinguists dealing with the linguistic phenomena outside borders are presented, as well as the efforts of contactologists on compiling a database of found forms of lexical influences by majority languages on idioms outside borders. The second part of the article analyzes in more detail the structure of the corpus of majority language loan words in Serbian, Croatian and Slovenian contact varieties of Hungarian, while an initial analysis of joint loan words is conducted, with a special review of their common variation that is the result of different influences of different majority language norms in the northern belt of ex-Yugoslavia. It is concluded that out of all seven varieties outside borders, the Croatian idiom is most heterogeneous from the aspect of the influence of majority languages, which requires a somewhat nuanced approach to further work.